The Role of Unemployment in Triggering Internal Labor Migration - George McCarthy (Levy Economics Institute of Bard College, 1992)
George McCarthy's paper explores the internal migration of labor in response to structural changes in the U.S. economy. He presents an empirical study of the relationship between wage determination and the migration decision co evaluate the role of both spiral wage differences and unemployment in motivating migration. Also, the paper assesses the relative homogeneity of the population pertaining to migration and wage determination. Orthodox analyses label the economic actor as an autonomous agent seeking to maximize lifetime utility. McCarthy uses data from the National Longitudinal Survey of the Labor Market Experience of Youth to assess the unemployment and wage motivations for migratory behavior among young males. The findings suggest that unemployment (e.g. the condition of being unemployed at point of origin and the unemployment rate at the point of destination) plays a larger role in prompting migration than spatial wage differences, and heterogeneity exists within the population with regard to migration.for example, it is implied that a person who has migrated previously is more prone to migrate again. The results challenge the validity of regarding labor and capital mobility as similarly motivated. Moreover, the conclusion is in contrast to the human capital view of migration as a voluntary investment decision: Wakin to the decision of labor to work or starve, migration involves the decision to move or adapt to a lower standard of living. To treat this as a voluntary decision is ludicrous." The public policy responses to address this problem can employ two distinct lines of attack: enhance the mobility of labor (e.g. increase skill or education levels) and minimize the social costs of mobility, or impede the mobility of capital by weakening its bargaining position through legislative action.
Keywords: 330